(3JHYjO GdYdeGA Yf JbQjH GdCeQGAs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYdeGA hQKI GdCfHjGA CeG HYO ajbhd Cf Gddg SHMGfg eG CYXe HQgGfg ai bhdg (B:" (3hdG JQcfhG Edi GdPjf XdehG aJeSce GdfGQ heGdce ef Ohf Gddg ef ChdjGA s
(3BNQgG (B:s
(3hjhGXH Ydi KHhJ GdbOe ai ebGe GdQLGA hjhGXH Ydi cKQg GdMeO hGdKfGA ai GdSQGA hGdVQGA hGONdfG GdLfI Bejf HQMeJc jG CQMe GdQGMejf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3fSNI fSNJ ef NW GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdeLGejYs